KELANCARAN PROSEDURAL MATEMATIS SISWA DALAM MENYELESAIKAN SOAL OPERASI BENTUK ALJABAR DI SEKOLAH MENENGAH PERTAMA - Damayanti, Eka; Sugiatno, Sugiatno; Sayu, Silvia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract The aim of this research is to describe the procedural fluency mathematic of students in solving algebraic operations. In this research, the procedural fluency based on two aspects: the students’ knowledge of procedural and the knowledge of using the procedural in the proper time to solve algebraic operations. The method of research used case study as the qualitative method. The subject of research were some junior high school students who lived around the researcher’s environment. The instrument of research consist of major instrument (the researcher) and supporting instrument (test and interview). Based on the result of research, the researcher found that the students’ knowledge of procedural fluency mathematic was not fluent enough. It is proven by the students’ answers. Most of them made mistake in answering the circumference of a rectangle and in operating unlike terms. Moreover, the students also confused when and how to use the procedural in solving algebraic operations. They were not consistent in operating like terms and unlike terms. In addition, they could not explain the correct reasons in using the procedural mathematic to solve algebraic operations.  Keywords: Procedural Fluency, Problem Solving, Algebraic Operations